2020
DOI: 10.1021/acs.energyfuels.0c02671
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Torrefaction on Properties of Pellets Produced from Woody Biomass

Abstract: Torrefaction has been recognized as a promising strategy to improve handling and storage properties of wood-based pellets, thus producing a uniform-quality commodity with high energy density and hydrophobicity. In this work, pellets produced from spruce stem wood, bark, and forest residues were torrefied in a bench-scale tubular reactor at 225 and 275 °C with two residence times (30 and 60 min). The effects of torrefaction on general properties, grindability, mechanical properties, hydrophobicity, and microstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
47
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 39 publications
7
47
1
Order By: Relevance
“…With increasing torrefaction temperature and residence time, mass yield, and energy yield decreased, weight loss and enhancement factor increased in HQ and LQ pellets. As stated in Wang's study [49], it has been revealed that the temperature is more effective on torrefaction efficiency than the residence time. The increase in temperature and residence time caused the loss of mass by removing the moisture content and volatiles.…”
Section: Torrefaction Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…With increasing torrefaction temperature and residence time, mass yield, and energy yield decreased, weight loss and enhancement factor increased in HQ and LQ pellets. As stated in Wang's study [49], it has been revealed that the temperature is more effective on torrefaction efficiency than the residence time. The increase in temperature and residence time caused the loss of mass by removing the moisture content and volatiles.…”
Section: Torrefaction Resultsmentioning
confidence: 85%
“…This shows that high torrefaction temperature and low residence time can replace low torrefaction temperature and high residence time. Increasing temperature and residence time decreased the O:C and H:C ratios of the pellets, causing an increase in the HHV and having better combustion characteristics [49]. As a result of the torrefaction process, the atomic ratios of high-quality pellets have progressed in a relatively linear direction (R 2 :0.93) due to their smooth shape and homogeneous physical properties.…”
Section: Torrefaction Resultsmentioning
confidence: 99%
“…Such positive effects are mainly due to hemicellulose decomposition. The hemicellulose is rich in hydroxyl groups (including carboxylic and phenolic groups), which can form a hydrogen bond with water increasing bonded water content [30,32]. When hemicellulose is decomposed because of depolymerization, demethoxylation, and bond cleavage reactions, these groups are removed as well.…”
Section: Peat Thermal-upgrading Methodsmentioning
confidence: 99%
“…When hemicellulose is decomposed because of depolymerization, demethoxylation, and bond cleavage reactions, these groups are removed as well. As a result, fuel becomes hydrophobic and more fungal-resistant [32]. In addition, changes in chemical composition (decrease in available nutrients and production of toxic chemicals) the resistance to biodegradation increases [30].…”
Section: Peat Thermal-upgrading Methodsmentioning
confidence: 99%
“…Another option is to use low-grade steam for a pulp and paper mill system to achieve partial drying of the biomass (Erixon and Bjorklund 2017). A related option to consider is torrefaction (Nosek et al 2017;Mostafa et al 2019;Wang et al 2020), which entails heating up of the material to a range of about 200 to 300 C (Picchio et al 2020). Torrefaction, which can be carried out either before or after compressing the material into pellets, results not only in water removal, but also in partial decomposition of hemicellulose, yielding higher density and lower tendency of the material to absorb moisture from the air during storage.…”
Section: Before Pulping Biomass Pelletsmentioning
confidence: 99%